Pulmonary arteriovenous malformation (PAVM) reperfusion after percutaneous embolization: Sensitivity and specificity of non-enhanced CT. Issue 1 (January 2016) - Bélanger, Chantale; Chartrand-Lefebvre, Carl; Soulez, Gilles; Faughnan, Marie E.; Tahir, Muhammad Ramzan; Giroux, Marie-France; Gilbert, Patrick; Perreault, Pierre; Bouchard, Louis; Oliva, Vincent L.; Therasse, Eric
Abstract: Purpose: To evaluate the sensitivity and specificity of non-enhanced chest CT to detect reperfusion after pulmonary arteriovenous malformation (PAVM) embolization. Materials and methods: The Institutional Review Board approved this retrospective HIPAA-compliant study and waived the need for patient consent. All consecutive patients who underwent PAVM embolization between January 2000 and April 2011 were included. Complex PAVMs and patients without available pre- and/or post-embolization CT were excluded. PAVM artery, aneurysm and vein diameters were measured on non-enhanced chest CT before and after PAVM embolization. Pulmonary angiography (PA) was the reference standard to assess PAVM reperfusion. Reperfusion detection was analyzed with receiver operating characteristic (ROC) curves according to percentage of diameter reduction cut-off. Inter-observer concordance was ascertained with intra-class correlation coefficients (ICCs). Results: Out of 68 patients with PAVM embolizations, 42 (62%) had 108 PAVMs that met inclusion/exclusion criteria. Areas under the ROC curves for PAVM reperfusion detection were 0.84, 0.87, and 0.78, respectively, for PAVM artery, aneurysm and vein ( p  > 0.05). Sensitivity varied between 51% and 56%, and specificity between 86% and 98% for the <30% diameter reduction cut-off. Sensitivity was between 98% and 100%, and specificity, between 20% and 47% for the <70% diameter reduction cut-off. ICCs for inter-observer concordance were 0.58, 0.88 and 0.68 for percentage reduction of PAVM artery, aneurysm and vein, respectively. Conclusion: PAVM diameter reduction cut-offs of <30% and <70%, to detect PAVM reperfusion on non-enhanced CT reported in the literature, would respectively result in low sensitivity and specificity.